2020
DOI: 10.1101/2020.04.19.20071415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of control strategies on COVID-19 pandemic and the SIR model based forecasting in Bangladesh

Abstract: Background COVID-19 is transmitting worldwide drastically and infected nearly two and half million of people so far. Till date 2144 cases of COVID-19 is confirmed in Bangladesh till 18 th April though the stage-3/4 transmission is not validated yet. MethodsTo project the final infection numbers in Bangladesh we used the SIR mathematical model. Confirmed cases of infection data were obtained from Institute of Epidemiology, Disease Control and Research (IEDCR) of Bangladesh ResultsThe confirmed cases in Banglade… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 16 publications
0
24
0
1
Order By: Relevance
“…Median age data presented that developing countries hold more young populations compared to developed countries. Young population always have tendencies to go outside and making them vulnerable age group (32). Therefore, test positive rates were high in developing countries where median age is below 30 years ( Figure 1C).…”
Section: Socioeconomic and Demographic Determinants Of Covid-19 Test mentioning
confidence: 99%
“…Median age data presented that developing countries hold more young populations compared to developed countries. Young population always have tendencies to go outside and making them vulnerable age group (32). Therefore, test positive rates were high in developing countries where median age is below 30 years ( Figure 1C).…”
Section: Socioeconomic and Demographic Determinants Of Covid-19 Test mentioning
confidence: 99%
“…Median age data indicated that developing countries have younger populations compared to developed countries. The young population has tendencies to go outside, making them a vulnerable age group (32). Therefore, positive test rates were high in developing countries where the median age is below 30 years ( Figure 1C).…”
Section: Socioeconomic and Demographic Determinants Of Covid-19 Positmentioning
confidence: 99%
“…Healthcare personnel are also being infected in all countries regardless of the country's economic status and demographic characters ( 24 , 31 ). Several disease susceptibility patterns and predictions are also made to understand trends of infections, death, and recovery patterns ( 6 , 32 ) and factors that influence transmission and fatalities ( 6 ). The associations of different environmental factors have also been investigated ( 6 , 33 , 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…But with the implementation of the various epidemic control methods in Bangladesh, the "randomly mixed" condition for virus transmission within the population has been violated. Currently, a few different R 0 estimations have been reported ranging between 1.4 to 3.0 [23,24,25] for the country. But due to the intervention mechanism, the original method to compute susceptible population from the R 0 cannot be followed.…”
Section: Adjustment Of Covid-19 Dynamics In Herd Immunitymentioning
confidence: 99%